Photoluminescent core-shell particles of organic dye in silica - Ethiraj, Anita S.; Hebalkar, Neha; Kharrazi, Sharmin; Urban, J.; Sainkar, S. R.; Kulkarni, S. K. (Journal of Luminescence, 2005)
Using a single silica precursor, Rhodamine 6G organic dye molecules have been entrapped in silica particles resulting into core-shell particles of similar to 500 nm diameter. Energy dispersive X-ray analysis, X-ray photoelectron spectroscopy and transmission electron microscopy analysis reveals that dye molecules are trapped inside the silica particles. Photoluminescence investigations show that highly luminescent and photostable core-shell particles are formed. Such core-shell particles can be easily suspended in water and would be useful for a variety of applications. However, there is a blue shift in the photolumineseence wavelength in case of core-shell particles compared to bare dye powder sample. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: core-shell; Luminescence; Nanoparticles; photoemission; RH06G dye; tetraethylorthosilicate (TEOS)

Study of correlation of structural and surface properties with electrochemical behaviour in carbon aerogels - Hebalkar, Neha; Arabale, G.; Sainkar, S. R.; Pradhan, S. D.; Mulla, Imtiaz S.; Vijayamohanan, K.; Ayyub, P.; Kulkarni, S. K. (Journal of Materials Science, 2005)
Carbon aerogel is a promising material for electrochemical double layer capacitors. In this paper carbon aerogels prepared by subcritical drying method are investigated for the change in the structure and surface properties at different pyrolysis temperatures. The important relations between structure, morphology, surface area and electrical properties were studied using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), surface area measurement and cyclic voltametry. It is shown that structure and the surface functional groups play important role in enhancement of electrochemical capacitance. The specific capacitance achieved was 114 F/gm which is quite large value for subcritically prepared carbon aerogels without any kind of activation process. (c) 2005 Springer Science + Business Media, Inc.

Highly photostable dye entrapped core-shell particles - Ethiraj, Anita S.; Kharrazi, Sharmin; Hebalkar, Neha; Urban, J.; Sainkar, S. R.; Kulkarni, S. K. (Materials Letters, 2007)
Organic dye namely Coumarin 7 has been entrapped in silica particles using a single silica precursor viz. tetraethylorthosilicate. Both bare Coumarin 7 dye and dye incorporated core-shell particles were studied. Investigations of these core-shell composites were carried out using different characterization techniques such as energy dispersive X-ray analysis, X-ray photoelectron spectroscopy and transmission electron microscopy. It has been shown that the photostability of dye molecules is improved along with an increase in photoluminescence. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: core-shell; coumarin 7 dye; Luminescence; photostability; tetraethylorthosilicate